MAGICAL REALISM-LIKE IN SHAKESPEARE'S A MIDSUMMER NIGHT'S DREAM - Dio Catur Prasetyohadi; Hat Pujiati; Irana Astutiningsih (Badan Pengembangan dan Pembinaan Bahasa, 2018)
This article uses concepts of magical realism by Wendy B. Faris to analyze Shakespeare's A Midsummer Night's Dream. We analyze elements of magical realism of the work in mapping discourses between the text and the real life. The chosen material object that published earlier than the theory we chose make this work contributes to describe the trace of the civilization development; event of in-betweeness of human consciousness. However, we have found that A Midsummer Night’s Dream is only a magical realism-like mode, since realism is dominant in the text as the trace of modernity. Meanwhile, the characteristics of Magical Realism that is postulated by Faris is in-between realism and fantasy as a trace of transition era; modern to postmodern.Abstrak: Artikel ini menggunakan konsep-konsep realism magis oleh Wendy B. Faris untuk menganalisis “A Midsummer Night’s Dream” karya Shakespeare. Kami menganalisis elemen-elemen realism magis yang ada dalam karya untuk memetakan wacana-wacana yang ada antara teks dan kenyataan. Pemilihan objek materi yang telah dipublikasi lebih awal dari kelahiran teori yangkami pilih ini berkontribusi untuk menjelaskan jejak perkembanan peradaban Kebudayaan; peristiwa keberantaraan pada kesadaran manusia. Namun demikian, kami menemukan bahwa “A Midsummer Night’s Dream” hanyalah moda tulisan Serupa Realisme Magis, karena dominan teks lebih pada realisme yang merupakan jejak dari modernitas. Sementara syarat realism magis yang ditawarkan Faris adalah keberantaraan realisme dan fantasi sebagai jejak era transisi modern menuju postmodern.